Ginsenoside Rg1 in Parkinson’s disease: from basic research to clinical applications - Wang, Qianyan; Wei, Lei; Chen, Guanghui; Chen, Qiang (Frontiers in Pharmacology, 2025)
This review provides an in-depth exploration of the potential of Ginsenoside Rg1 in the treatment of Parkinson’s disease (PD). The emphasis of this article was the therapeutic mechanisms of Rg1, which involved the reduction of inflammation, antioxidant properties, support for neuronal survival and regeneration, regulation of cellular energy processes, and enhancement of autophagic pathways. Rg1 may protect neurons and improve both motor and cognitive impairments associated with PD through multiple mechanisms. However, challenges exist in the clinical application of Rg1, such as low bioavailability as well as a lack of comprehensive long-term safety and efficacy data. This article also reviewed network pharmacology analyses published previously to identify and explore the potential molecular targets of Rg1 in PD treatment, while evaluating strategies such as drug delivery technologies, optimizing administration routes, and combination therapies. Ultimately, this review highlights the necessity for large-scale clinical trials to validate the clinical efficacy of Rg1 and discusses its potential for PD treatment clinically.